Remarks for Yale Workshop on Global Trends and Challenges : Understanding Global Imbalances - Cooper, Richard N. (World Bank, Washington, DC, 2017)
This paper argues that global imbalances in current account positions are a natural consequence of globalization of financial markets and of demographic trends, particularly in Europe and in East Asia. Those societies are aging rapidly, with declining numbers of young adults. On both counts savings should be high and investment weak, resulting in excess saving. With globalization of capital markets, this excess saving will naturally seek secure investment opportunities abroad. The U.S. economy, where demographic trends are markedly different (due in part to immigration of young adults), offers a good combination of yield, liquidity, and security for this excess savings, which in time will be liquidated to finance consumption in old age. Thus the large 'imbalance' does not obviously reflect disequilibria in the world economy, but rather a current phase of intertemporal trade.